A (não) marcação de tense em língua brasileira de sinais - Lorena Mariano Borges de Figueiredo (2020)
This dissertation aims at investigating if and how tense is encoded in Brazilian Sign Language and its relation to aspectual marking in the verb domain. Assuming the notion of tenselessness and the tests proposed by Lin (2012), we demonstrate that Libras shows the same morphosyntactic characteristics of others tenseless languages, such as Chinese. Additionally, based on Wilbur (2003, 2008), Lourenço (2018, 2019) and Karabüklü (2018), we designed two experiments to test how Libras signers interpret time reference when a sentence does not contain time expressions: a judgment test of sentences and a pilot eye-tracking study. We were interested in verifying if aspectual morphology on the verb may contribute or even determine the time reference reading of the sentence. The results show that Libras is a morphologically tenseless language, like Chinese, Vietnamese, Guarani, Malay and TİD (as claimed by Karabüklü). However, it can and do construct time reference by using time adverbials or time expressions and time interpretation can interact with the aspect reading of the predicate.